2023
DOI: 10.1186/s12891-023-06766-3
|View full text |Cite
|
Sign up to set email alerts
|

How safe are intra-articular corticosteroid injections to the hip?

Laura Elisa Streck,
Sebastian Braun,
Kimi Spilo
et al.

Abstract: Background Intra-articular corticosteroid injections (ICSI) are an effective symptomatic treatment for osteoarthritis of the hip. However, the safety of ICSI has been questioned and a relatively high risk for septic arthritis, rapidly progressive osteoarthritis (RPIO) and periprosthetic joint infections (PJI) in patients undergoing subsequent total hip arthroplasty (THA) have been suggested. Methods This is a retrospective evaluation of 682 hips th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Streck, LE et al (2023) 8 showed the rate of RPIO was 0.6%. The current findings suggest that if ICSI is performed under sterile conditions, the risk for septic arthritis or PJI following THA, even in patients with multiple ICSI or ICSI within 3 months prior to surgery, is minimal.…”
Section: Resultsmentioning
confidence: 97%
“…Streck, LE et al (2023) 8 showed the rate of RPIO was 0.6%. The current findings suggest that if ICSI is performed under sterile conditions, the risk for septic arthritis or PJI following THA, even in patients with multiple ICSI or ICSI within 3 months prior to surgery, is minimal.…”
Section: Resultsmentioning
confidence: 97%